(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The article examines the characteristic features of the novels and analyzes the novelistic works of the German writer Wilhelm Hauff. The work of Wilhelm Hauff occupies a special place in the literary process in Germany. Having emerged at the turn of epochs, namely at the end of the “aesthetic period”, his work reflected the features of the transitional time, combining heterogeneous style tendencies, and makes it possible to see in it important links in the national history of the development of the genre. Wilhelm Hauff entered the history of literature, primarily as a storyteller. But in his fabulous creativity one senses the tendencies of another artistic language and another genre form.